USE OF EDMODO IN MATHEMATICS LEARNING IN HIGHER EDUCATION - R Amalia & Risna (Universitas Samudra, 2019)
In the field of Mathematics Education, the development of this technology makes it possible to innovate in Mathematics learning in the form of e-learning. No exception to tertiary institutions as the highest level of education after primary and secondary school. Lecturers can finance students in tertiary institutions who on average have a smartphone to carry out e-learning in lectures. One learning application that can be used in learning mathematics is Edmodo application. Edmodo application allows lectures to be carried out in mobile learning with unlimited space and time. This application can be used as a medium of learning mathematics in providing material, assignments and projects to students that can be monitored without having to be in the lecture hall. The purpose of writing this study article is to find out how to use Edmodo application in learning mathematics in tertiary institutions. The method used is a descriptive method with studies that link studies from various literatures. In the end, it is hoped that this study can be utilized in the development of mathematics learning, especially in tertiary institutions.